An Aqueous Redox Flow Battery Based on Neutral Alkali Metal Ferri/ferrocyanide and Polysulfide Electrolytes. Issue 1 (13th November 2015) - Wei, Xiaoliang; Xia, Guan-Guang; Kirby, Brent; Thomsen, Ed; Li, Bin; Nie, Zimin; Graff, Gordon G.; Liu, Jun; Sprenkle, Vincent; Wang, Wei
Abstract : We have demonstrated a new ferri/ferrocyanide – polysulfide (Fe/S) flow battery, which employs less corrosive, relatively environmentally benign neutral alkali metal ferri/ferrocyanide and alkali metal polysulfides as the active redox couples. A cobalt nanoparticle – decorated graphite felt was used at the polysulfide side as the catalyst. Excellent electrochemical performance was successfully acquired in the Fe/S flow cells with high cell efficiencies (99% coulombic efficiency and ∼74% energy efficiency) and good cycling stability over extended charge/discharge operations. The positive half-cell appears to be the performance – limiting side in the Fe/S flow battery determined by using a carbon cloth probe. The inexpensive redox materials and possibly cell part materials can lead to reduced capital cost, making the Fe/S flow battery a promising cost-effective energy storage technology candidate.